High-temperature electromagnetic functional composite coating and preparation method thereof

By adopting a multi-layer structure of high-temperature electromagnetic functional composite coating, using thermal spray composite ceramic materials and a variety of electromagnetic functional materials, the existing coating's narrow absorption frequency band and insufficient performance are solved, and efficient electromagnetic wave absorption and performance improvement are achieved.

CN119824354APending Publication Date: 2025-04-15AVIC BEIJING INST OF AERONAUTICAL MATERIALS

Patent Information

Application Number
CN202510058806.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing high-temperature electromagnetic functional coatings have narrow absorption frequency bands, low absorption losses, poor temperature resistance, poor corrosion resistance, poor environmental media resistance and poor mechanical properties, which cannot meet the requirements of complex application conditions.

Method used

A high-temperature electromagnetic functional composite coating with a multi-layer structure includes an adhesive layer, a protective layer, a functional layer and a surface layer. The functional layer is made of thermally sprayed composite ceramic material, including a variety of electromagnetic functional materials to broaden the absorption frequency band, and improve the temperature, corrosion resistance and mechanical properties of the coating through multi-layer structural design and material combination.

Benefits of technology

The coating effectively absorbs electromagnetic waves, improves temperature resistance, corrosion resistance and environmental adaptability, extends service life, and enhances the mechanical properties of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824354A_ABST
    Figure CN119824354A_ABST
Patent Text Reader

Abstract

The invention relates to a high-temperature electromagnetic functional composite coating and a preparation method thereof, belongs to the technical field of high-temperature electromagnetic functional materials, and solves the problems of narrow absorption frequency band, low absorption loss, poor temperature resistance, poor corrosion resistance, poor environmental medium resistance and poor mechanical property of the existing high-temperature electromagnetic functional coating. From the surface of the substrate from inside to outside, the high-temperature electromagnetic functional composite coating comprises a bonding layer, a protective layer, a functional layer and a surface layer, and the functional layer is made of a thermal spraying composite ceramic material; the multi-layer structure of each layer of the composite coating is mutually coordinated and matched, so that the temperature resistance, the corrosion resistance and the environmental medium resistance of the coating are improved, the electromagnetic wave absorption efficiency is improved, and the service life is prolonged; in addition, the composite ceramic material forming the functional layer has multiple loss mechanisms, the electromagnetic wave absorption frequency band is further widened, and the absorption loss is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-temperature electromagnetic functional materials, and in particular to a high-temperature electromagnetic functional composite coating and a preparation method thereof. Background Art

[0002] With the advancement of science and technology, electromagnetic waves are increasingly widely used, which not only endangers human health and interferes with the normal use of equipment, but also becomes increasingly diverse as a means of detection. Correspondingly, higher requirements are placed on coating materials that interfere, shield and absorb electromagnetic waves. The application environment of electromagnetic functional coating materials is becoming more and more harsh. In practical applications, they need to have adjustable electromagnetic functions to adapt to environmental changes.

[0003] At present, the electromagnetic wave absorption band of electromagnetic functional coating materials is narrow and the absorption loss is limited, which cannot meet the use requirements. To address this problem, people are committed to using composite electromagnetic absorption materials containing a variety of electromagnetic functional materials to prepare electromagnetic functional coatings, increase the material's loss mechanism for electromagnetic waves, and broaden the absorption band.

[0004] However, in practical applications, the electromagnetic functional coating composed of composite electromagnetic absorption materials has poor mechanical properties and low bonding strength (~6MPa). When the environment changes, including ambient temperature, medium and other factors, the coating is prone to cohesive fracture. Especially under harsh conditions of use, the coating is prone to problems such as shedding and failure, which affects the electromagnetic wave absorption efficiency and service life.

[0005] Therefore, it is necessary to find an electromagnetic functional coating material with excellent performance in many aspects, including electromagnetic function, temperature resistance, corrosion resistance, environmental medium resistance and mechanical properties, so as to adapt to the higher requirements of electromagnetic wave absorbing coating materials put forward by increasingly complex application conditions. Summary of the invention

[0006] In view of the above analysis, an embodiment of the present invention aims to provide a high-temperature electromagnetic functional composite coating and a preparation method thereof, so as to solve at least one of the technical problems of existing high-temperature electromagnetic functional coatings, such as narrow absorption band, low absorption loss, poor temperature resistance, poor corrosion resistance, poor environmental medium resistance and poor mechanical properties.

[0007] In the first aspect, an embodiment of the present invention provides a high-temperature electromagnetic functional composite coating, which, from the inside to the outside of the substrate surface, includes a bonding layer, a protective layer, a functional layer and a surface layer, wherein the material of the functional layer includes a thermally sprayed composite ceramic material, and the composite ceramic material includes a matrix material and a plurality of functional materials dispersed in the matrix material.

[0008] Furthermore, the thickness of the functional layer is 1.25-1.4 mm, and from the inside to the outside of the substrate surface, the functional layer includes: a first absorbing layer, a wave-transmitting layer and a second absorbing layer, wherein the material of the first absorbing layer and the second absorbing layer is the composite ceramic material, and the thickness of the wave-transmitting layer is 0.35-0.4 mm.

[0009] Furthermore, the matrix material is at least one of mullite, zirconia, cordierite, silicon dioxide, silicon nitride, and boron nitride, and the functional material includes SiBCNFe or / and SiCuCN, Ti3SiC2 or / and TiC, CNTs or / and carbon fiber, MoSi2 or / and Si3N4, ZnO or / and MnO2, and YSZ.

[0010] Furthermore, in terms of mass percentage, the contents of the components in the composite ceramic material are: SiBCNFe 8%-10%, Ti3SiC2 15%-18%, CNTs 2%-5%, MoSi 25%-8%, ZnO 4%-6%, YSZ 22%-27%, and the remainder mullite.

[0011] Furthermore, the composite ceramic material is a spherical powder with a particle size of 25-110 μm, and the bulk density of the spherical powder is 0.4-2.2 g / cm 3 , fluidity is 30-50s / 50g.

[0012] Furthermore, the material of the wave-transmitting layer is one of aluminum oxide, mullite, zirconium oxide, cordierite, silicon dioxide, silicon nitride, and boron nitride.

[0013] Furthermore, the material of the bonding layer is metal alloy powder, selected from one or more of NiCrAlYSi, NiCrAlY, NiCrCoAlY, nickel-chromium alloy, and cobalt-chromium alloy, with a thickness of 0.1-0.2 mm.

[0014] Furthermore, the bonding layer is a heat-treated bonding layer.

[0015] Furthermore, the material of the protective layer is a heat-resistant resin selected from one or more of modified polysilazane resin, modified polysiloxane, modified siloxane, and modified silicone resin, and has a thickness of 0.03-0.05 mm.

[0016] Furthermore, the surface layer is made of a wave-transmitting and high-temperature resistant material selected from high-entropy rare earth double silicate (La 1 / 6 Hf 1 / 6Ta 1 / 6 Yb 1 / 6 Er 1 / 6 G 1 / 6)2Si2O7, mullite, BSAS (BaO-SrO-Al2O3-SiO2), alumina, YSZ, with a thickness of 0.05-0.1mm.

[0017] In a second aspect, an embodiment of the present invention provides a method for preparing the high-temperature electromagnetic functional composite coating, the method comprising: (1) Spraying bonding layer; (2) Spraying protective layer; (3) spraying a functional layer, wherein the material of the functional layer comprises a thermally sprayed composite ceramic material, wherein the composite ceramic material comprises a matrix material and a plurality of electromagnetic functional materials dispersed in the matrix material; (4) Spraying surface layer.

[0018] Furthermore, step (1) also includes heat treating the sprayed bonding layer.

[0019] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects: 1. The multilayer structures of the electromagnetic functional composite coating of the present invention coordinate with each other to improve the temperature resistance, corrosion resistance, and environmental medium resistance of the coating while achieving effective absorption of electromagnetic waves by the coating, and enhance the environmental adaptability of the coating, so as to improve the electromagnetic wave absorption efficiency and extend the service life; the bonding layer enables the functional layer to be firmly adhered to the surface of the substrate to form a continuous coating, which determines the basic physical properties of the functional layer, including bonding, adhesion, mechanical strength and environmental resistance, etc., and plays a role in transition of the thermal expansion coefficient between the substrate and the functional layer, so as to improve the temperature resistance and thermal shock resistance of the composite coating; the protective layer covers the surface of the bonding layer to prevent corrosive substances or environmental media from entering the interior of the bonding layer; the surface layer covers the surface of the functional layer to prevent corrosive substances or environmental media from entering the functional layer.

[0020] Among them, among the composite ceramic materials constituting the functional layer, a variety of electromagnetic functional materials enable the composite coating to have a variety of loss mechanisms, broaden the electromagnetic wave absorption band, improve the absorption loss, and assume the controllability of the electromagnetic function; the functional layer is prepared by thermal spraying using composite ceramic powder materials, and the thermal spraying process can improve the bonding strength between the ceramic powder and the substrate, achieve controllable coating thickness, and simplify the coating preparation process, reducing the impact on the substrate material; in addition, the various electromagnetic functional materials are all temperature-resistant materials, which is beneficial to improving the temperature resistance of the electromagnetic functional composite coating of the present invention.

[0021] 2. The functional layer in the electromagnetic functional composite coating of the present invention has a trap-type structure. A wave-transmitting layer is provided between two wave-absorbing layers composed of composite ceramic materials. The wave-transmitting layer can guide the electromagnetic waves that have been initially attenuated by the second wave-absorbing layer to penetrate into the coating. The first wave-absorbing layer further absorbs and attenuates the electromagnetic waves that have penetrated in, thereby increasing the contact opportunities between the electromagnetic waves and the subsequent wave-absorbing layers, achieving multiple absorption of the electromagnetic waves entering the coating, and enhancing the wave-absorbing effect. Through the combination of the multi-layer structure of the functional layer, the width of the coating absorption band is further broadened, and the problem of the narrow absorption band of the high-temperature electromagnetic functional coating is better solved. In addition, the design of the wave-transmitting layer can also optimize the impedance matching between materials, and further reduce the reflection loss of electromagnetic waves at the interface.

[0022] 3. The various electromagnetic functional materials in the composite ceramic material described in the present invention cooperate and coordinate with each other to play a role in broadening the electromagnetic wave absorption band. In addition to limiting the composition of the composite ceramic material, the present invention also limits the content of each component; the composite ceramic material not only achieves the broadening of the electromagnetic wave absorption band by increasing the loss mechanism, but also takes into account that the different physical and chemical properties of different electromagnetic functional materials may affect the morphology, structure and performance of the composite ceramic material obtained after combination, thereby affecting its electromagnetic function and service life in practical applications. The present invention needs to limit the content of the components.

[0023] 4. The composite ceramic material provided by the present invention is a spherical powder with good fluidity and compactness, wherein the bulk density of the composite ceramic powder is 0.4-2.2 g / cm 3 The fluidity is 30-50s / 50g, which is beneficial to reduce the porosity of the prepared coating and improve the mechanical properties of the coating; in addition, the particle size and uniformity of the spherical powder will affect the density and bonding degree of the prepared coating. The particle size of the composite ceramic powder of the present invention is 25-110μm. The ceramic powder with a particle size in this range makes the coating have stronger bonding strength and lower porosity, and in the thermal spraying process, it will also reduce the evaporation loss of elements and improve the protective performance and service life of the coating.

[0024] 5. The heat-treated metal bonding layer in the electromagnetic functional composite coating of the present invention forms a dense metal oxide layer on the surface, which prevents corrosive substances from entering the bonding layer through the pores and causing corrosion failure of the bonding layer; The bonding layer is sprayed, cured and coated with a heat-resistant resin to fill the pores, so that the connection between the bonding layer and the electromagnetic functional coating is more uniform and dense, and corrosive substances are further prevented from entering the bonding layer; A heat-resistant and wave-transmitting material is sprayed on the surface of the functional layer to form a surface layer located at the outermost layer of the composite coating. The surface layer isolates the functional layer from the external environment, prevents oxidation of the electromagnetic functional material under high temperature conditions, and improves the temperature resistance of the coating. It can also prevent corrosive substances from entering the electromagnetic functional composite coating, further improving the coating's environmental resistance such as salt spray resistance and solvent oil resistance.

[0025] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The accompanying drawings are only used for the purpose of illustrating specific embodiments and are not to be considered as limiting the present invention. In the entire drawings, the same reference symbols represent the same components; Figure 1 This is a schematic diagram of the structure of the high-temperature electromagnetic functional composite coating of the present invention; Figure 2 is a SEM image of the composite ceramic powder 1 of Preparation Example 1; Figure 3 is a SEM image of the composite ceramic powder 2 of Preparation Example 2; Figure 4 is a SEM image of the composite ceramic powder 3 of Preparation Example 3; Figure 5 This is a SEM image of the composite ceramic powder 4 prepared in Preparation Example 4; Figure 6 is a SEM image of the composite ceramic powder 5 prepared in Preparation Example 5; Figure 7 This is a SEM image of the composite ceramic powder 6 prepared in Preparation Example 6; Figure 8 is a SEM image of the composite ceramic powder 7 prepared in Preparation Example 7; Fig. 9 Environmental resistance test diagram of the composite coating 1 prepared in Example 1, (a) salt spray resistance, (b) solvent oil resistance; Fig.10 Environmental resistance test diagram of the composite coating 2 prepared in Example 2, (a) salt spray resistance, (b) solvent oil resistance; Fig.11 Environmental resistance test diagram of the composite coating 3 prepared in Example 3, (a) salt spray resistance, (b) solvent oil resistance; Fig.12The environmental resistance test diagram of the composite coating 4 prepared in Example 4 is (a) salt spray resistance, (b) solvent oil resistance; Fig.13 Environmental resistance test diagram of the composite coating 5 prepared in Example 5, (a) salt spray resistance, (b) solvent oil resistance; Fig.14 The environmental resistance test diagram of the composite coating 6 prepared in Example 6 is (a) salt spray resistance, (b) solvent oil resistance; Fig.15 Environmental resistance test diagram of the composite coating 7 prepared in Example 7, (a) salt spray resistance, (b) solvent oil resistance; Fig.16 Environmental resistance test diagram of the composite coating 8 prepared in Example 8, (a) salt spray resistance, (b) solvent oil resistance; Fig.17 The environmental resistance test diagram of the composite coating 9 prepared in comparative example a, (a) salt spray resistance, (b) solvent oil resistance; Fig.18 The environmental resistance test diagram of the composite coating 10 prepared in comparative example b is (a) salt spray resistance, (b) solvent oil resistance; Fig.19 The environmental resistance test diagram of the composite coating 11 prepared in comparative example c is (a) salt spray resistance, (b) solvent oil resistance; Reference numerals: 1. Surface layer; 2. Functional layer; 2-1. First absorbing layer; 2-2. Transparent layer; 2-3. Second absorbing layer; 3. Protective layer; 4. Adhesive layer. DETAILED DESCRIPTION

[0027] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0028] With the increasingly widespread application of electromagnetic waves, higher requirements are placed on coatings that shield and absorb electromagnetic waves, and the application environment of electromagnetic functional coatings is becoming more and more harsh. Because the single loss mechanism of the electromagnetic functional materials that constitute the coating limits its absorption performance of electromagnetic waves, people are committed to studying composite electromagnetic absorption materials composed of multiple electromagnetic functional materials to broaden the absorption band.

[0029] However, in practical applications, the electromagnetic functional coating composed of composite electromagnetic absorption materials has poor mechanical properties and low bonding strength (~6MPa). When the environment changes, including ambient temperature, medium and other factors, the coating is prone to cohesive fracture. Especially under harsh conditions of use, the coating is prone to problems such as shedding and failure, which affects the electromagnetic wave absorption efficiency and service life.

[0030] Therefore, the present invention also provides an electromagnetic functional composite coating, wherein the composite coating has the controllability of electromagnetic function, and its structure is as follows: Figure 1 As shown, from the inside to the outside of the substrate surface, the composite coating specifically includes: a bonding layer 4, a protective layer 3, a functional layer 2 and a surface layer 1, wherein the material of the functional layer comprises a thermally sprayed composite ceramic material, and the composite ceramic material includes a matrix material and a plurality of electromagnetic functional materials dispersed in the matrix material.

[0031] The base material of the present invention is one of high temperature alloy and stainless steel.

[0032] The multilayer structures of the electromagnetic functional composite coating of the present invention cooperate with each other to improve the temperature resistance, corrosion resistance, and environmental medium resistance of the coating while achieving effective absorption of electromagnetic waves by the coating, and enhance the environmental adaptability of the coating, so as to improve the electromagnetic wave absorption efficiency and extend the service life.

[0033] Specifically, the bonding layer enables the functional layer to adhere firmly to the surface of the substrate to form a continuous coating, which determines the basic physical properties of the functional layer, including bonding, adhesion, mechanical strength and environmental resistance, etc., and plays a role in transition of the thermal expansion coefficient between the substrate and the functional layer to improve the temperature resistance and thermal shock resistance of the composite coating.

[0034] Specifically, the protective layer covers the surface of the bonding layer to prevent corrosive substances or environmental media from entering the interior of the bonding layer.

[0035] Specifically, the surface layer covers the surface of the functional layer to prevent corrosive substances or environmental media from entering the functional layer.

[0036] Specifically, in the composite ceramic material constituting the functional layer, a variety of electromagnetic functional materials enable the composite coating to have a variety of loss mechanisms, broaden the electromagnetic wave absorption band, increase the absorption loss, and assume the controllability of the electromagnetic function.

[0037] In addition, the functional layer is prepared by thermal spraying of composite ceramic powder material and wave-transmitting material. The thermal spraying process can improve the bonding strength between the ceramic powder and the substrate, realize controllable coating thickness, simplify the coating preparation process, and reduce the impact on the substrate material; the various electromagnetic functional materials are all temperature-resistant materials, which is beneficial to the improvement of the temperature resistance of the electromagnetic functional composite coating of the present invention; the material of the wave-transmitting layer should be resistant to high temperatures, have suitable electromagnetic parameters, and be able to transmit the electromagnetic waves that need to be absorbed.

[0038] Specifically, the wave-transmitting material may be one of alumina, mullite, zirconia, cordierite, silicon dioxide, silicon nitride, and boron nitride.

[0039] According to some preferred embodiments of the present invention, the material of the wave-transmitting layer is aluminum oxide.

[0040] Furthermore, the thickness of the functional layer is 1.25-1.4 mm, and from the inside to the outside of the substrate surface, the functional layer includes: a first absorbing layer, a wave-transmitting layer and a second absorbing layer, wherein the material of the first absorbing layer and the second absorbing layer is the composite ceramic material, and the thickness of the wave-transmitting layer is 0.35-0.4 mm.

[0041] It should be noted that the functional layer in the electromagnetic functional composite coating of the present invention has a trap-type structure, and a wave-transmitting layer is provided in the middle of the two wave-absorbing layers composed of composite ceramic materials. The wave-transmitting layer can guide the electromagnetic waves that have been initially attenuated by the second wave-absorbing layer to penetrate into the coating. The first wave-absorbing layer further absorbs and attenuates the electromagnetic waves that have penetrated in, thereby increasing the contact opportunities between the electromagnetic waves and the subsequent wave-absorbing layers, achieving multiple absorption of the electromagnetic waves entering the coating, and enhancing the wave-absorbing effect. Through the combination of the multi-layer structure of the functional layer, the width of the absorption band of the coating is further broadened, and the problem of the narrow absorption band of the high-temperature electromagnetic functional coating is better solved.

[0042] In addition, the present invention limits the thickness of the functional layer to 1.25-1.4 mm. If the functional layer is too thin, the electromagnetic function of the coating will be poor and the wave absorption performance will be poor. If the functional layer is too thick, although the maximum absorption loss will be increased, the wave absorption bandwidth will be reduced, and it will also cause the weight of the coating system to increase significantly and the surface density of the coating to increase.

[0043] The present invention tests the electromagnetic parameters of the thermal sprayed composite ceramic powder material and the wave-transmitting material, uses CST software to calculate the simulated reflectivity of the three-layer structure of the electromagnetic functional layer, and obtains the simulated reflectivity in the frequency range of 4-18 GHz. Comprehensive analysis shows that the thickness range of the wave-transmitting layer is 0.35-0.4 mm.

[0044] It should be noted that most of the existing high-temperature resistant electromagnetic functional composite coatings adopt a single-layer functional layer system. The absorption band of the functional layer is narrow and the wave absorption performance is limited. It is often necessary to increase the thickness to improve its wave absorption performance. This application uses CST software to simulate the reflectivity calculation of the multi-layer structure wave absorbing coating, and optimizes the design of the functional layer for different frequency ranges; by precisely controlling the electromagnetic parameters of each layer (such as dielectric constant, magnetic permeability, etc.), better impedance matching is achieved, thereby reducing the reflection of electromagnetic waves at the interface and improving the efficiency of electromagnetic waves entering the coating; the materials between different layers can produce complementary effects, and through the interaction between layers, the propagation path and attenuation times of electromagnetic waves in the coating are increased, achieving more efficient electromagnetic wave absorption, broadening the wave absorption band of the overall coating, and improving the wave absorption performance of the coating.

[0045] According to some preferred embodiments of the present invention, the thicknesses of the functional layers are 1.25 mm, 1.32 mm, and 1.4 mm, respectively; the thicknesses of the wave-transmitting layers are 0.35 mm, 0.37 mm, and 0.4 mm, respectively.

[0046] Furthermore, the matrix material of the composite ceramic material is one or more of mullite, zirconia, cordierite, silicon dioxide, silicon nitride, and boron nitride, and the functional material includes SiBCNFe or / and SiCuCN, Ti3SiC2 or / and TiC, CNTs or / and carbon fiber, MoSi2 or / and Si3N4, ZnO or / and MnO2, and YSZ.

[0047] According to some preferred embodiments of the present invention, the matrix material is mullite, and the functional materials include SiBCNFe, Ti3SiC2, CNTs, MoSi2, ZnO and YSZ.

[0048] The present invention evenly disperses a variety of electromagnetic functional materials into the matrix material. The various electromagnetic functional materials have a variety of loss mechanisms, broaden the electromagnetic wave absorption band, improve the absorption loss, and assume the controllability of the electromagnetic function, as shown in Table 1.

[0049] Specifically, SiBCNFe and SiCuCN have magnetic loss and dielectric loss mechanisms, CNTs and carbon fibers have resistive loss mechanisms, and Ti3SiC2, MoSi2, ZnO, TiC, Si3N4, AlN, and MnO2 have dielectric loss mechanisms.

[0050] Furthermore, the various electromagnetic functional materials used in the present invention cooperate and coordinate with each other to broaden the electromagnetic wave absorption band. In addition to limiting the composition of the composite ceramic material, the present invention also limits the content of each component.

[0051] According to some preferred embodiments of the present invention, the contents of the components in the composite ceramic material are, by mass percentage, SiBCNFe 8%-10%, Ti3SiC215%-18%, CNTs 2%-5%, MoSi25%-8%, ZnO 4%-6%, YSZ22%-27%, and the remainder mullite.

[0052] The composite ceramic material not only achieves the broadening of the electromagnetic wave absorption band by increasing the loss mechanism, but also takes into account that the different physical and chemical properties of different electromagnetic functional materials may affect the morphology, structure and performance of the composite ceramic material obtained after combination, thereby affecting its electromagnetic function and service life in practical applications.

[0053] It should be noted that in order for the absorbing material to absorb electromagnetic waves, it must meet impedance matching conditions and attenuation conditions. Impedance matching requires that the dielectric constant and magnetic permeability of the coating match within the entire frequency range to reduce the reflection of electromagnetic waves at the incident interface. When absorbers with multiple loss mechanisms constitute the composite absorber system of the present invention, a large number of interfaces and defects cause electromagnetic waves to be reflected and transmitted multiple times, thereby allowing as many waves as possible to enter the material body, thereby improving impedance matching and being beneficial to the absorption of electromagnetic waves.

[0054] It should be noted that the composite ceramic material of the present invention includes absorbing materials with different loss mechanisms, wherein the magnetic loss absorber mainly absorbs electromagnetic waves through a suitable magnetic permeability to generate magnetic loss; the dielectric loss absorber uses a suitable dielectric constant to absorb electromagnetic waves and generates dielectric loss; the resistive loss absorber converts electromagnetic wave energy into thermal energy loss through mechanisms such as electron clouds and lattice vibrations in the material; magnetic loss, dielectric loss and resistive loss do not exist in isolation, but are mutually synergistic and act together. The absorbers with different loss mechanisms form a complex electromagnetic field distribution in the coating, and the electromagnetic waves are affected by multiple loss mechanisms when propagating therein. This synergistic effect can significantly improve the absorbing performance of the coating, so that it can achieve high absorption rate in a wider frequency band. The proportion of magnetic loss, dielectric loss and resistive loss materials is accurately controlled to balance the contribution of dielectric loss, magnetic loss and resistive loss. Generally, the best combination of component ratios is found through experiments and simulations to achieve the best synergistic effect.

[0055] Specifically, the composite ceramic material of the present invention is a spherical powder with good fluidity and compactness, which is beneficial to reduce the porosity of the coating obtained by thermal spraying, increase the density of the coating, and improve the mechanical properties of the coating and the bonding strength between the coating and the substrate; the bulk density of the composite ceramic powder of the present invention is 0.4-2.2g / cm 3 , fluidity is 30-50s / 50g.

[0056] The present invention also limits the particle size of the spherical powder. The size and uniformity of the particle size will affect the density and bonding of the prepared coating. In the thermal spraying process of the material, the particle size will also affect the evaporation loss of the elements, thereby affecting the protective performance and service life of the coating.

[0057] Specifically, the particle size of the composite ceramic powder of the present invention is limited to 25-110 μm. If the particle size is too small, the fluidity of the powder is poor, and the evaporation loss of elements will increase, affecting the composition and density of the coating; if the particle size is too large, it is easy to cause the powder to be insufficiently melted in the high-temperature heat flow, affecting the deposition efficiency; in addition, the powder particle size distribution should not be too wide to avoid uneven heating of the powder during thermal spraying.

[0058] The present invention can adopt EDS, XRD, laser particle size analyzer, Hall flow meter, SEM and other testing technologies to characterize the composition and content, structure and performance of the thermal spraying composite ceramic material.

[0059] The following is an explanation of the performance parameters of high temperature electromagnetic functional coatings: Absorption bandwidth: The absorption bandwidth usually refers to the frequency range within which the reflection loss of the material is lower than a certain value (such as -10dB, -7dB, etc.); therefore, the -7dB absorption bandwidth means that within this frequency range, the reflection loss of the material is lower than -7dB; the wider the bandwidth, the more stable and powerful the material's ability to absorb electromagnetic waves within this frequency range.

[0060] Maximum absorption loss: When the electromagnetic wave is incident on the surface of the material, the material can absorb and convert the maximum value of the electromagnetic wave energy into other forms of energy (such as heat energy), the vertical coordinate value corresponding to the lowest point in the reflectivity curve.

[0061] Bonding strength: It is the strength of the bonding between the coating and the substrate, that is, the force required for a unit area of ​​the coating to peel off from the substrate (or intermediate coating); the higher the coating bonding strength, the stronger the bonding between the coating and the substrate, and the better the coating's peeling resistance and impact resistance.

[0062] Porosity: The ratio of the pore area in the coating cross section to the entire coating area is one of the important indicators of coating quality and will directly affect the performance and service life of the coating.

[0063] 700℃ (300h): Heat resistance performance assessment. The heat resistance test is carried out in accordance with GB / T 1735 "Determination of Heat Resistance of Paints and Varnishes". The sample is placed in a 700℃ muffle furnace and taken out after 300 hours of heat preservation to observe whether the coating has cracks or cracks.

[0064] 900℃ (100h): Heat resistance performance assessment. The heat resistance test is carried out in accordance with GB / T 1735 "Determination of Heat Resistance of Paints and Varnishes". The sample is placed in a 900℃ muffle furnace, and taken out after 100 hours of heat preservation to observe whether the coating has cracks or cracks.

[0065] Among them, by optimizing the structure of the high-temperature electromagnetic functional coating and limiting the materials of the first and second absorbing layers in the functional layer, the absorbing bandwidth (-7dB) of the high-temperature electromagnetic functional coating of the present invention is 1-4.2GHz, that is, when the maximum loss is -7dB, the electromagnetic wave frequency width that the coating can absorb; the maximum absorption loss is (-7)-(-11.5)dB; the bonding strength between the high-temperature alloy substrate is 6.5-14.5Mpa; the porosity is 10-26.5%; the maximum temperature resistance of the coating is as high as 900℃; Figure 9-11It can be seen that the high-temperature electromagnetic functional coating also has good environmental resistance.

[0066] Furthermore, in order to achieve effective bonding between the electromagnetic functional coating and the substrate material, the present invention adopts a material with good temperature resistance, good oxidation resistance and a suitable thermal expansion coefficient as a bonding layer, which not only achieves a firm bond between the substrate and the electromagnetic functional coating, but also reduces the difference in thermal expansion coefficients between the absorbing electromagnetic functional coating and the substrate in practical applications, thereby improving bonding strength and preventing the coating from falling off.

[0067] Specifically, the raw material constituting the bonding layer is metal alloy powder, selected from one or more of NiCrAlYSi, NiCrAlY, NiCrCoAlY, nickel-chromium alloy, and cobalt-chromium alloy.

[0068] The present invention limits the thickness of the bonding layer to 0.1-0.2 mm. If the bonding layer is too thin, it cannot play a role in transition of the thermal expansion coefficient, and the temperature resistance and thermal shock resistance of the coating system are reduced; if the bonding layer is too thick, it will cause the weight of the coating system to increase significantly and the surface density of the coating to increase.

[0069] According to some preferred embodiments of the present invention, the metal alloy powder is NiCrAlYSi, and the thicknesses are 0.1 mm, 0.15 mm, and 0.2 mm, respectively.

[0070] Furthermore, in order to prevent corrosive substances from entering the interior of the bonding layer, the bonding layer obtained by spraying is heat treated to form a dense metal oxide layer on the surface of the bonding layer, thereby preventing corrosive substances from entering the interior of the bonding layer through the pores and causing corrosion failure of the bonding layer.

[0071] Furthermore, in order to make the connection between the bonding layer and the electromagnetic functional coating more uniform and dense, and further prevent corrosive substances from entering the electromagnetic functional composite coating, the present invention uses a heat-resistant resin to spray and cure the bonding layer to form a protective layer to fill the pores and improve the density and mechanical properties of the coating.

[0072] Specifically, the heat-resistant resin constituting the protective layer has good compactness and excellent environmental resistance after curing, and can be selected from one or more of modified polysilazane resin, modified polysiloxane, modified siloxane, and modified silicone resin.

[0073] The present invention limits the thickness of the protective layer to 0.03-0.05mm. If the protective layer is too thin, it cannot completely cover the bonding layer and cannot play a role in protecting the bonding layer, and the environmental resistance of the coating, such as salt spray resistance and solvent oil resistance, is reduced. Because the thermal expansion coefficient of the protective layer is relatively low, if the protective layer is too thick, it will cause the thermal expansion coefficient of the coating system to mismatch, and the temperature resistance and thermal shock resistance of the coating system will be reduced.

[0074] According to some preferred embodiments of the present invention, the material of the protective layer is modified polysilazane resin, and the thicknesses are 0.03 mm, 0.04 mm, and 0.05 mm, respectively.

[0075] Furthermore, in order to isolate the electromagnetic functional layer from the external environment, prevent oxidation of the electromagnetic functional material under high temperature conditions, and improve the temperature resistance of the coating, the present invention uses a temperature-resistant and wave-transparent material to spray on the surface of the electromagnetic functional coating to form a surface layer located at the outermost layer of the composite coating; in addition, the surface layer can also further prevent corrosive substances from entering the electromagnetic functional composite coating.

[0076] Specifically, the material constituting the surface layer is an inert material with low oxygen permeability, a thermal expansion coefficient that matches well with the rest of the coating, and good phase structure stability, and no phase transition occurs in the working environment; it can be selected from high entropy rare earth disilicate (La 1 / 6 Hf 1 / 6 Ta 1 / 6 Yb 1 / 6 Er 1 / 6 G 1 / 6 )2Si2O7, mullite, BSAS (BaO-SrO-Al2O3-SiO2), alumina, one or more of YSZ.

[0077] The present invention limits the thickness of the surface layer to 0.05-0.1 mm. If the surface layer is too thin, it will not be able to completely cover the functional layer and cannot play a role in protecting the functional layer, and the environmental resistance of the coating, such as salt spray resistance and solvent oil resistance, will be reduced; if the surface layer is too thick, the weight of the coating system will increase significantly and the surface density of the coating will increase.

[0078] According to some preferred embodiments of the present invention, the material of the surface layer is high entropy rare earth disilicate (La 1 / 6H 1 / 6 Ta 1 / 6 Yb 1 / 6 Er 1 / 6 G 1 / 6 )2Si2O7, with thicknesses of 0.05mm, 0.07mm and 0.1mm respectively.

[0079] The present invention adopts GJB 2038A-2011 standard, GB / T 5210 standard, GB / T 15749-1995 standard, GB / T 1771 standard and GB / T 9274 standard to test the electromagnetic function (absorption bandwidth, maximum absorption loss, etc.), temperature resistance, bonding strength, porosity and other properties of the electromagnetic functional composite coating.

[0080] The present invention also provides a method for preparing the composite coating, the method comprising: (1) Spraying a bonding layer on the substrate surface; (2) Spraying a protective layer on the bonding layer; (3) spraying a functional layer on the protective layer, wherein the material of the functional layer is a composite ceramic; (4) Spray the surface layer on the corresponding functional layer.

[0081] Furthermore, step (1) also includes heat treating the sprayed bonding layer.

[0082] According to a preferred embodiment of the present invention, the method is specifically: (1) Spraying of bonding layer: The spraying powder is NiCrAlYSi metal powder, and the spraying process is supersonic flame spraying. The specific parameters are: oxygen flow rate 1700-1800SCFH, kerosene flow rate 25-28L / h, carrier gas flow rate 12-17SCFH, powder feeding rate 6-10r / min, spraying distance 320-340mm, and spraying thickness 0.1-0.2mm; Heat treatment of the bonding layer: Place the bonding layer sample in a vacuum sintering furnace. Do not cross-contaminate the samples. Wash the vacuum sintering furnace three times before sintering. The sintering temperature is 1050-1100℃, the sintering time is 90-120min, the heating rate is 5℃ / min, and the samples are cooled with the furnace. (2) The protective layer was prepared by air spraying and curing process. The spraying powder was modified polysilazane resin. The spraying process parameters were: spray gun pressure 0.15MPa-0.25MPa, spray gun diameter 1.0mm-1.3mm, spray gun distance 15cm-30cm from the sample, and 3 sprayings. The curing process parameters are: maintain at 80-100°C for -10 min, maintain at 120-130°C for 10 min, and the heating rate is 1°C / min; (3) The three-layer structure of the functional layer is made by plasma spraying process, specifically: The first absorbing layer is sprayed, and the spraying powder is a composite ceramic material, and the composition and content thereof are: SiBCNFe 8%-10%, Ti3SiC215%-18%, CNTs 2%-5%, MoSi25%-8%, ZnO 4%-6%, YSZ 22%-27%, and the balance is mullite; the spraying process parameters are: current 600-620A, main gas Ar flow rate 45-50NLPM, auxiliary gas H2 flow rate 16-18NLPM, carrier gas Ar flow rate 4-5NLPM, powder feeding rate 18-23g / min, spraying distance 105-115mm, and spraying thickness 0.55-0.6mm; Spray the wave-transmitting layer, the spraying powder is alumina, the spraying process parameters are: current 560-580A, main gas Ar flow 42-45NLPM, auxiliary gas H2 flow 11-13NLPM, carrier gas Ar flow 5-7NLPM, powder feeding rate 20-25g / min, spraying distance 110-120mm, spraying thickness 0.35-0.4mm; Spraying the second absorbing layer, the spraying powder is the same as the powder used for spraying the first absorbing layer, the process parameters are: current 600-620A, main gas Ar flow rate 45-50NLPM, auxiliary gas H2 flow rate 16-18NLPM, carrier gas Ar flow rate 4-5NLPM, powder feeding rate 18-23g / min, spraying distance 105-115mm, spraying thickness 0.35-0.4mm; (4) Spraying surface layer: The plasma spraying-physical vapor deposition (PS-PVD) process is adopted, and the spraying powder is high entropy rare earth double silicate (La 1 / 6 Hf 1 / 6 Ta 1 / 6 Yb 1 / 6 Er 1 / 6 G 1 / 6 )2Si2O7, spraying process parameters: the flow rate of main gas Ar is 40-60SLPM, the flow rate of auxiliary gas He is 70-90SLPM, the flow rate of carrier gas Ar is 15-18SLPM, the current is 2500-3000A, the powder feeding rate is 8-12g / min, the spraying distance is 1000-1200mm, and the spraying thickness is 0.05-0.1mm.

[0083] According to some preferred embodiments of the present invention, the method for preparing the thermal spraying composite ceramic material comprises: (1) According to the composition of the composite ceramic material, a matrix raw material, a functional raw material, deionized water and a binder are mixed to obtain a mixed slurry; (2) spray granulating the mixed slurry to obtain agglomerated powder; (3) sintering the agglomerated powder; (4) The powder sintered in step (3) is subjected to plasma spheroidization treatment and sieved.

[0084] Specifically, in step (1), the mixing step is as follows: at room temperature, the raw materials are accurately weighed according to the mass ratio and placed in a stirring container, and then deionized water and a binder are added to the stirring container and stirred to obtain a uniformly mixed slurry.

[0085] Furthermore, the stirring speed is 100-150 rpm and the time is 5-7 h.

[0086] Furthermore, in order to control the morphology, density and forming and sintering properties of the particles obtained by subsequent spray granulation, it is necessary to limit the amount of deionized water and the amount of binder in the mixed slurry. Among them, the proportion of the binder should be appropriate to ensure that the viscosity of the slurry is moderate, which is conducive to the spheroidization and densification of the powder after granulation.

[0087] Specifically, the mass of deionized water in the mixed slurry of the present invention is 1-1.2 times the mass of the raw material; the mass of the binder is 0.5-1% of the mass of the raw material.

[0088] Furthermore, the binder of the present invention is compatible with the material, ensures a high powder output rate, does not affect the performance of the spray granulation process, and can be selected from one or more of polyvinyl alcohol, phenolic resin, polyacrylamide, and polypropylene. In view of the fact that polyvinyl alcohol also acts as a dispersant during the raw material mixing process, in some preferred embodiments of the present invention, the binder is polyvinyl alcohol.

[0089] The spray granulation process adopted by the method of the present invention not only has high production efficiency, but also can achieve regulation of the morphology and particle size of the obtained composite ceramic powder by controlling the solid content of the slurry and the process parameters of the granulation process.

[0090] Specifically, in step (2), the process parameters of the spray granulation of the present invention are as follows: inlet temperature 340-350°C, outlet temperature 100-110°C, spray disk speed 30-40Hz, and feed speed 35-45rpm.

[0091] Among them, the inlet and outlet temperatures of spray granulation affect the droplet drying efficiency and the performance of the separated material after drying. Too high a temperature will reduce the effect of the binder, affect the cohesive strength of the agglomerated separation, and easily cause the particles to be too fine; too low a temperature will easily cause wall sticking, and cause the powder particles to be insufficiently strong and easy to break.

[0092] In addition, the rotation speed of the spray disc will affect the atomization effect of the slurry and the particle size of the powder obtained. The faster the rotation speed, the smaller the atomized droplets and the higher the drying efficiency. The feed speed will affect the size of the droplets and the uniformity of the particles. For example, a feed speed that is too fast may cause the particles to be too large or irregular in shape; a feed speed that is too slow may cause the particles to be too small or stick together, and reduce production efficiency.

[0093] According to some preferred embodiments of the present invention, in the process parameters of the spray granulation, the inlet temperature is 340°C, 345°C or 350°C, the outlet temperature is 100°C, 105°C or 110°C, the spray disc speed is 30Hz, 35Hz or 40Hz, and the feed rate is 35rpm, 40rpm or 45rpm.

[0094] Furthermore, in order to improve the cohesive strength between small particles inside the agglomerated powder obtained by spray granulation, the present invention performs a sintering treatment on the agglomerated powder.

[0095] Specifically, in step (3), the specific steps of the sintering treatment are: placing the crucible containing the agglomerated powder in a sintering furnace, and sintering in a protective atmosphere: sintering at a temperature of 550-950°C for 2-4h; sintering at a temperature of 1100-1500°C for 2-5h; the present invention adopts sintering the agglomerated powder at high and low temperatures, which is beneficial to removing the binder in the powder and homogenizing the particles, better promoting the densification of the particles and improving the mechanical properties, and avoiding the generation of defects.

[0096] According to some preferred embodiments of the present invention, the sintering conditions are sintering at 950°C for 2h + sintering at 1100°C for 2h, or sintering at 950°C for 2h + sintering at 1150°C for 2h; or sintering at 950°C for 2h + sintering at 1200°C for 2h. Furthermore, the present invention also performs plasma spheroidization treatment on the sintered agglomerated powder to improve the fluidity of the powder, and further improve the bonding strength between small particles inside the thermal spraying powder, improve the density of the coating made of thermal spraying composite ceramic material, reduce the porosity of the coating, and improve the mechanical properties of the coating.

[0097] Specifically, in step (4), the process parameters of the plasma spheroidization are: current 600-650A, main gas (Ar) 100-110SCFH, auxiliary gas (H2) 7-9SCFH, carrier gas (Ar) 8-10SCFH, powder feeding rate 2.0-3.0r / min.

[0098] According to some preferred embodiments of the present invention, the conditions for plasma spheroidization are: current 600A, main gas (Ar) 100SCFH, auxiliary gas (H2) 7SCFH, carrier gas (Ar) 8SCFH, and powder feeding rate 2.0r / min; or: current 625A, main gas (Ar) 105SCFH, auxiliary gas (H2) 8SCFH, carrier gas (Ar) 9SCFH, and powder feeding rate 2.5r / min; or: current 650A, main gas (Ar) 110SCFH, auxiliary gas (H2) 9SCFH, carrier gas (Ar) 10SCFH, and powder feeding rate 3.0r / min.

[0099] Furthermore, the method of the present invention further comprises screening the agglomerated powder after spheroidization to obtain powder with a particle size and range that meet the requirements.

[0100] Specifically, the agglomerated powder is placed in an oscillating sieve analyzer, and the sieving parameters are: amplitude 2-3 mm, sieving time 3-5 min, and rest time 10 s, to obtain a thermal spray composite ceramic powder with a particle size range of 25-110 μm.

[0101] The technical solution of the present invention is further explained below in conjunction with specific embodiments.

[0102] Preparation Example 1 A method for preparing a thermal spray composite ceramic powder 1 comprises: (1) Weigh 160 g of SiBCNFe, 300 g of Ti3SiC2, 40 g of CNTs, 100 g of MoSi2, 80 g of ZnO, 440 g of YSZ, 880 g of mullite, 2000 g of deionized water, and 10 g of polyvinyl alcohol into a stirring container, and stir at a stirring speed of 100 r / min for 5 h to obtain a mixed slurry; (2) using a spray dryer to spray granulate the mixed slurry obtained in step (1), the spray granulation process parameters are: inlet temperature 340°C, outlet temperature 100°C, spray disk speed 30Hz, feed speed 35rpm, to obtain spherical agglomerated powder; (3) placing the spherical agglomerated powder in a crucible, and placing the crucible in an atmosphere sintering furnace for sintering. The sintering process is as follows: sintering at 950°C for 2 h, sintering at 1100°C for 2 h, and cooling in the furnace under an Ar protective atmosphere; (4) The sintered agglomerated powder is fed into a plasma spheroidization device. The process parameters of plasma spheroidization are: current 600A, main gas (Ar) 100SCFH, auxiliary gas (H2) 7SCFH, carrier gas (Ar) 8SCFH, and powder feeding rate 2.0r / min; (5) The spheroidized powder was placed in an oscillating sieving instrument for sieving. The sieving parameters were: amplitude 2 mm, sieving time 3 min, and rest time 10 s, to obtain a thermal sprayed composite ceramic powder 1.

[0103] The SEM image of thermal sprayed composite ceramic powder 1 is shown in Figure 1 As shown; after testing, the average particle size of the composite ceramic powder 1 is 80μm and the bulk density is 1.2g / cm 3 , fluidity is 32s / 50g.

[0104] Preparation Example 2 A method for preparing a thermal spray composite ceramic powder 2 comprises: (1) Weigh 180 g of SiBCNFe, 330 g of Ti3SiC2, 70 g of CNTs, 130 g of MoSi2, 100 g of ZnO, 490 g of YSZ, 700 g of mullite, 2200 g of deionized water, and 15 g of polyvinyl alcohol, place them in a stirring container, and stir them at a stirring speed of 120 r / min for 6 h to obtain a mixed slurry; (2) using a spray dryer to spray granulate the mixed slurry obtained in step (1), the spray granulation process parameters are: inlet temperature 345°C, outlet temperature 105°C, spray disk speed 35Hz, feed speed 40rpm, to obtain spherical agglomerated powder; (3) placing the spherical agglomerated powder in a crucible, and placing the crucible in an atmosphere sintering furnace for sintering. The sintering process is as follows: sintering at 950°C for 2 h, sintering at 1150°C for 2 h, and cooling in the furnace under an Ar protective atmosphere; (4) The sintered agglomerated powder is fed into a plasma spheroidization device. The process parameters of plasma spheroidization are: current 625A, main gas (Ar) 105SCFH, auxiliary gas (H2) 8SCFH, carrier gas (Ar) 9SCFH, and powder feeding rate 2.5r / min; (5) The spheroidized powder was placed in an oscillating sieving instrument for sieving. The sieving parameters were: amplitude 2.5 mm, sieving time 4 min, and rest time 10 s, to obtain a thermal sprayed composite ceramic powder 2.

[0105] The SEM image of thermal sprayed composite ceramic powder 2 is shown in Figure 2 As shown in the figure, after testing, the average particle size of the composite ceramic powder 2 is 82 μm, and the bulk density is 1.5 g / cm 3 , fluidity is 38s / 50g.

[0106] Preparation Example 3 A method for preparing a thermal spray composite ceramic powder 3 comprises: (1) Weigh 200 g of SiBCNFe, 360 g of Ti3SiC2, 100 g of CNTs, 160 g of MoSi2, 120 g of ZnO, 540 g of YSZ, 520 g of mullite, 2400 g of deionized water, and 20 g of polyvinyl alcohol and place them in a stirring container, stir at a stirring speed of 150 r / min for 7 h to obtain a mixed slurry; (2) using a spray dryer to spray granulate the mixed slurry obtained in step (1), the spray granulation process parameters are: inlet temperature 350° C., outlet temperature 110° C., spray disk speed 40 Hz, feed speed 45 rpm, to obtain spherical agglomerated powder; (3) placing the spherical agglomerated powder in a crucible, and placing the crucible in an atmosphere sintering furnace for sintering. The sintering process is as follows: sintering at 950°C for 2 h, sintering at 1200°C for 2 h, and cooling in the furnace under an Ar protective atmosphere; (4) The sintered agglomerated powder is fed into a plasma spheroidization device. The process parameters of plasma spheroidization are: current 650A, main gas (Ar) 110SCFH, auxiliary gas (H2) 9SCFH, carrier gas (Ar) 10SCFH, and powder feeding rate 3.0r / min; (5) The spheroidized powder was placed in an oscillating sieving instrument for sieving. The sieving parameters were: amplitude 3 mm, sieving time 5 min, and rest time 10 s, to obtain a thermal sprayed composite ceramic powder 3.

[0107] The SEM image of thermal sprayed composite ceramic powder 3 is shown in Figure 3 As shown in the figure, after testing, the average particle size of the composite ceramic powder 3 is 78 μm, and the bulk density is 2.0 g / cm 3 , fluidity is 42s / 50g.

[0108] Preparation Example 4 The thermal spraying composite ceramic powder 4 is prepared by the same method as in Example 2, except that: in step (1), 180 g of SiBCNFe, 400 g of Ti3SiC2, 130 g of MoSi2, 100 g of ZnO, 490 g of YSZ, 700 g of mullite, 2200 g of deionized water, and 15 g of polyvinyl alcohol are placed in a stirring container and stirred at a stirring speed of 120 r / min for 6 h to obtain a mixed slurry; and then steps (2) to (5) are performed to finally obtain the thermal spraying composite ceramic powder 4.

[0109] The SEM image of thermal sprayed composite ceramic powder 4 is shown in Figure 4 As shown in the figure, after testing, the average particle size of the composite ceramic powder 4 is 68 μm, and the bulk density is 3.0 g / cm 3 , fluidity 60s / 50g.

[0110] Preparation Example 5 The thermal spraying composite ceramic powder 5 is prepared by the same method as in Example 2, except that the spheroidization process in step (4) is not included in the preparation process, and the thermal spraying composite ceramic powder 5 is finally obtained.

[0111] The SEM image of thermal sprayed composite ceramic powder 5 is shown in Figure 5 As shown in the figure, after testing, the average particle size of the composite ceramic powder 5 is 65 μm, and the bulk density is 1.1 g / cm 3 , fluidity 88s / 50g, powder surface is relatively rough.

[0112] Preparation Example 6 The thermal spraying composite ceramic powder 6 was prepared by the same method as in Example 2, except that: The sintering process in step (3) is: sintering at 450°C for 1 hour, sintering at 1000°C for 1 hour under Ar protective atmosphere, and cooling in the furnace; The plasma spheroidization process in step (4) is: current 550A, main gas (Ar) 85SCFH, auxiliary gas (H2) 5SCFH, carrier gas (Ar) 4SCFH, powder feeding rate 6r / min; finally, thermal spraying composite ceramic powder 6 is obtained.

[0113] The SEM photo of the thermal sprayed composite ceramic powder 6 is shown in FIG6 . After testing, it is found that the average particle size of the composite ceramic powder 6 is 66 μm and the bulk density is 3.1 g / cm 3 , fluidity 66s / 50g, some areas of the powder surface are densified, while some areas are not densified.

[0114] Preparation Example 7 The thermal sprayed composite ceramic powder 7 was prepared by the same method as in Example 2, except that the spray granulation process parameters in step (2) were: inlet temperature 245°C, outlet temperature 115°C, spray disk speed 50 Hz, feed rate 60 rpm, and spherical agglomerated powder was obtained; finally, the thermal sprayed composite ceramic powder 7 was obtained.

[0115] The SEM photo of the thermal sprayed composite ceramic powder 7 is shown in FIG7 . After testing, it is found that the average particle size of the composite ceramic powder 7 is 60 μm and the bulk density is 3.4 g / cm 3 , the fluidity is poor and cannot be tested. The poor sphericity of the powder leads to poor fluidity, which in turn leads to unstable powder feeding during the spheroidization process. After spheroidization, the powder surface is not completely densified and the powder strength is low.

[0116] Example 1 Preparation of electromagnetic functional composite coating 1, comprising: (1) Spraying a bonding layer on the surface of a high-temperature alloy substrate, the spraying powder is NiCrAlYSi metal powder, the spraying process is supersonic flame spraying, the spraying parameters are: oxygen flow rate 1700SCFH, kerosene flow rate 25L / h, carrier gas flow rate 12SCFH, powder feeding rate 6r / min, spraying distance 320mm, spraying thickness 0.1mm; The adhesive layer after spraying is heat treated, specifically including: placing the adhesive layer sample in a vacuum sintering furnace, preventing cross contamination between samples, and washing the vacuum sintering furnace three times before sintering; heating to 1050°C at a rate of 5°C / min, sintering for 90 minutes; cooling with the furnace; (2) Spray a protective layer on the surface of the heat-treated bonding layer. The raw material is a modified polysilazane resin with a solid content of 45%, 6000-7000 g / mol. The air spraying and curing process is used. Three sprayings are performed. The air spraying parameters are: spray gun pressure 0.15 MPa, spray gun diameter 1.0 mm, spray gun distance 15 cm from the sample, and curing process parameters are: heating at a rate of 1 °C / min, curing at 80 °C for 10 min, curing at 120 °C for 10 min, and a thickness of 0.04 mm. (3) Spraying an electromagnetic functional layer, which is divided into three layers: a first absorbing layer, an alumina layer, and a second absorbing layer. The first absorbing layer uses the composite ceramic powder 1 prepared in Preparation Example 1. The spraying process parameters are: current 600A, main gas Ar flow rate 45NLPM, auxiliary gas H2 flow rate 16NLPM, carrier gas Ar flow rate 4NLPM, powder feeding rate 18g / min, spraying distance 105mm, and spraying thickness 0.55mm. The spraying powder of the alumina layer is alumina with a particle size of 30-75μm. The spraying process parameters are: current 560A, main gas Ar flow rate 42NLPM, auxiliary gas H2 flow rate 11NLPM, carrier gas Ar flow rate 5NLPM, powder feeding rate 20g / min, spraying distance 110mm, and spraying thickness 0.35mm. The second absorbing layer uses the composite ceramic powder 1 prepared in Example 1, and the spraying process parameters are the same as those of the first absorbing layer, and the spraying thickness is 0.35 mm.

[0117] (4) Spraying surface layer, the spraying powder is high entropy rare earth double silicate (La 1 / 6 Hf 1 / 6 Ta 1 / 6 Yb 1 / 6 Er 1 / 6 G 1 / 6 )2Si2O7, the spraying process adopts plasma spraying-physical vapor deposition (PS-PVD) process, the spraying process parameters are: the flow rate of the main gas Ar is 40SLPM, the flow rate of the auxiliary gas He is 70SLPM, the flow rate of the carrier gas Ar is 15SLPM, the current is 2500, the powder feeding rate is 8g / min, the spraying distance is 1000mm, and the spraying thickness is 0.05mm.

[0118] Example 2 Preparation of electromagnetic functional composite coating 2, comprising: (1) Spraying a bonding layer on the surface of a high-temperature alloy substrate, the spraying powder is NiCrAlYSi metal powder, the spraying process is supersonic flame spraying, the spraying parameters are: oxygen flow rate 1750SCFH, kerosene flow rate 26L / h, carrier gas flow rate 15SCFH, powder feeding rate 8r / min, spraying distance 330mm, spraying thickness 0.15mm; The adhesive layer after spraying is heat treated, specifically including: placing the adhesive layer sample in a vacuum sintering furnace, preventing cross contamination between samples, and washing the vacuum sintering furnace three times before sintering; heating to 1070°C at a rate of 5°C / min, sintering for 100min; cooling with the furnace; (2) Spray a protective layer on the surface of the heat-treated bonding layer. The raw material is a modified polysilazane resin with a solid content of 45%, 6000-7000 g / mol. The air spraying and curing process is used. Three sprayings are performed. The air spraying parameters are: spray gun pressure 0.20 MPa, spray gun diameter 1.2 mm, spray gun distance 20 cm from the sample, and curing process parameters are: heating at a rate of 1 °C / min, curing at 90 °C for 10 min, curing at 125 °C for 10 min, and a thickness of 0.03 mm. (3) Spraying the electromagnetic functional layer, which is divided into three layers: a first absorbing layer, an aluminum oxide layer, and a second absorbing layer. The first absorbing layer uses the composite ceramic powder 1 prepared in Preparation Example 2. The spraying process parameters are: current 610A, main gas Ar flow rate 47NLPM, auxiliary gas H2 flow rate 17NLPM, carrier gas Ar flow rate 4.5NLPM, powder feeding rate 20g / min, spraying distance 110mm, and spraying thickness 0.57mm. The spraying powder of the alumina layer is alumina with a particle size of 30-75μm. The spraying process parameters are: current 570A, main gas Ar flow rate 43NLPM, auxiliary gas H2 flow rate 12NLPM, carrier gas Ar flow rate 6NLPM, powder feeding rate 22g / min, spraying distance 115mm, and spraying thickness 0.37mm. The second absorbing layer uses the composite ceramic powder 1 prepared in Example 1, and the spraying process parameters are the same as those of the first absorbing layer, and the spraying thickness is 0.38 mm.

[0119] (4) Spraying surface layer, the spraying powder is high entropy rare earth double silicate (La 1 / 6 Hf 1 / 6 Ta 1 / 6 Yb 1 / 6 Er 1 / 6 G 1 / 6 )2Si2O7, the spraying process adopts plasma spraying-physical vapor deposition (PS-PVD) process, the spraying process parameters are: the flow rate of the main gas Ar is 50SLPM, the flow rate of the auxiliary gas He is 80SLPM, the flow rate of the carrier gas Ar is 16SLPM, the current is 2700, the powder feeding rate is 10g / min, the spraying distance is 1100mm, and the spraying thickness is 0.07mm.

[0120] Example 3 Preparation of electromagnetic functional composite coating 3, comprising: (1) Spraying a bonding layer on the surface of a high-temperature alloy substrate, the spraying powder is NiCrAlYSi metal powder, the spraying process is supersonic flame spraying, and the spraying parameters are: oxygen flow rate 1800SCFH, kerosene flow rate 28L / h, carrier gas flow rate 17SCFH, powder feeding rate 10r / min, spraying distance 340mm, and spraying thickness 0.2mm; The adhesive layer after spraying is heat treated, specifically including: placing the adhesive layer sample in a vacuum sintering furnace, preventing cross contamination between samples, and washing the vacuum sintering furnace three times before sintering; heating to 1100°C at a rate of 5°C / min, sintering for 120min; cooling with the furnace; (2) Spray a protective layer on the surface of the heat-treated bonding layer. The raw material is a modified polysilazane resin with a solid content of 45%, 6000-7000 g / mol. The air spraying and curing process is used. Three sprayings are performed. The air spraying parameters are: spray gun pressure 0.25 MPa, spray gun diameter 1.3 mm, spray gun distance 30 cm from the sample, and curing process parameters are: heating at a rate of 1 °C / min, curing at 100 °C for 10 min, curing at 130 °C for 10 min, and a thickness of 0.05 mm. (3) Spraying the electromagnetic functional layer, which is divided into three layers: a first absorbing layer, an aluminum oxide layer, and a second absorbing layer. The first absorbing layer uses the composite ceramic powder 1 prepared in Preparation Example 3. The spraying process parameters are: current 620A, main gas Ar flow rate 50NLPM, auxiliary gas H2 flow rate 18NLPM, carrier gas Ar flow rate 5NLPM, powder feeding rate 23g / min, spraying distance 115mm, and spraying thickness 0.60mm. The spraying powder of the alumina layer is alumina with a particle size of 30-75μm. The spraying process parameters are: current 580A, main gas Ar flow rate 45NLPM, auxiliary gas H2 flow rate 13NLPM, carrier gas Ar flow rate 7NLPM, powder feeding rate 25g / min, spraying distance 120mm, and spraying thickness 0.40mm. The second absorbing layer uses the composite ceramic powder 1 prepared in Example 1, and the spraying process parameters are the same as those of the first absorbing layer, and the spraying thickness is 0.40 mm.

[0121] (4) Spraying surface layer, the spraying powder is high entropy rare earth double silicate (La 1 / 6 Hf 1 / 6 Ta 1 / 6 Yb 1 / 6 Er 1 / 6 G 1 / 6)2Si2O7, the spraying process adopts plasma spraying-physical vapor deposition (PS-PVD) process, the spraying process parameters are: the flow rate of the main gas Ar is 60SLPM, the flow rate of the auxiliary gas He is 90SLPM, the flow rate of the carrier gas Ar is 18SLPM, the current is 3000, the powder feeding rate is 12g / min, the spraying distance is 1200mm, and the spraying thickness is 0.10mm.

[0122] Example 4 Preparation of electromagnetic functional composite coating 4, comprising: The same method as in Example 1 is used, except that the raw materials of the first absorbing layer and the second absorbing layer in step (3) are composite ceramic powder 4.

[0123] Example 5 Preparation of electromagnetic functional composite coating 5, comprising: The same method as in Example 1 is used, except that the raw materials of the first absorbing layer and the second absorbing layer in step (3) are composite ceramic powder 5.

[0124] Example 6 Preparation of electromagnetic functional composite coating 6, comprising: The same method as in Example 1 is used, except that the raw materials of the first absorbing layer and the second absorbing layer in step (3) are composite ceramic powder 6.

[0125] Example 7 Preparation of electromagnetic functional composite coating 7, comprising: The same method as in Example 1 is used, except that the raw materials of the first absorbing layer and the second absorbing layer in step (3) are composite ceramic powder 7.

[0126] Example 8 Preparation of electromagnetic functional composite coating 8, comprising: The same method as in Example 1 was used, except that the particle size of the raw materials of the first absorbing layer and the second absorbing layer in the functional layer in step (3) was 120 μm.

[0127] Comparative Example a Preparation of electromagnetic functional composite coating 8, comprising: The same method as in Example 1 is used, except that the functional layer in step (3) only includes the first absorbing layer.

[0128] Comparative Example b The electromagnetic functional composite coating 10 is prepared, comprising: The same method as in Example 1 is used, except that step (2) is not included, that is, the obtained electromagnetic functional composite coating 10 does not include a protective layer.

[0129] Comparative Example c The electromagnetic functional composite coating 11 is prepared, comprising: The same method as in Example 1 is used, except that step (4) is not included, that is, the obtained electromagnetic functional composite coating 11 does not include a surface layer.

[0130] Test Case The electromagnetic function, bonding strength, porosity and temperature resistance of the electromagnetic functional composite coatings prepared in Examples 1-8 and Comparative Examples ac were tested to obtain the data shown in Table 1. The environmental resistance test was performed. Figure 9-19 As shown, the performance test methods and standards are as follows: Coating electromagnetic function test: According to GJB 2038A-2011 standard, the test is carried out using the bow frame method, and the electromagnetic function of the material is measured based on the principle of reflection and absorption of electromagnetic waves on the material surface; Adhesion by pull-off method: According to GB / T 5210 standard, the test column is bonded to the coating surface with adhesive, and then tensile stress is applied on a tensile testing machine to measure the tensile force required to destroy the adhesion unit area between the coating and the substrate, thereby evaluating the adhesion of the coating; Coating porosity test: GB / T 15749-1995 standard, using the intercept method in the quantitative metallographic manual determination method to determine the coating porosity, that is, the pores in the coating are regarded as one phase, and the coating entity is regarded as one phase, and the pore content in the three-dimensional space is inferred from the two-dimensional parameters measured in the metallographic grinding surface; Salt spray resistance: According to GB / T 1771 standard, the salt spray test is carried out for 192 hours at (35±1)℃ and 5% NaCl environment. After the test, take out the sample, wipe off the water marks / salt particles with absorbent cotton or soft paper, place it in the standard test environment for 30 minutes, and complete the appearance observation within 30 minutes; Resistance to solvent oil: According to GB / T 9274 standard, immerse the coating in solvent oil and conduct medium resistance test at (23±2)℃ for 7 days. After the test, take out the sample and wipe off the oil stain with absorbent cotton or soft paper (120# solvent gasoline is allowed to be dipped to remove solvent oil residue). After placing it under standard test environment for 30 minutes, complete the appearance observation within 30 minutes.

[0131] Table 1

[0132] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A high temperature electromagnetic functional composite coating, characterized in that: From the inside to the outside of the substrate surface, the composite coating includes a bonding layer, a protective layer, a functional layer and a surface layer, wherein the material of the functional layer comprises a thermally sprayed composite ceramic material, and the composite ceramic material includes a matrix material and a plurality of functional materials dispersed in the matrix material.

2. The composite coating according to claim 1, characterized in that: The thickness of the functional layer is 1.25-1.4 mm. From the inside to the outside of the substrate surface, the functional layer includes: a first absorbing layer, a wave-transmitting layer and a second absorbing layer, wherein the materials of the first absorbing layer and the second absorbing layer are the composite ceramic material, and the thickness of the wave-transmitting layer is 0.35-0.4 mm.

3. The composite coating according to claim 2, characterized in that: The matrix material is at least one of mullite, zirconia, cordierite, silicon dioxide, silicon nitride, and boron nitride, and the functional material includes SiBCNFe or / and SiCuCN, Ti3SiC2 or / and TiC, CNTs or / and carbon fiber, MoSi2 or / and Si3N4, ZnO or / and MnO2, and YSZ.

4. The composite coating according to claim 3, characterized in that: Calculated by mass percentage, the contents of the components in the composite ceramic material are: SiBCNFe 8%-10%, Ti3SiC2 15%-18%, CNTs 2%-5%, MoSi2 5%-8%, ZnO4%-6%, YSZ 22%-27%, and the balance mullite.

5. The composite coating according to claim 4, characterized in that: The composite ceramic material is a spherical powder with a particle size of 25-110 μm, and the bulk density of the spherical powder is 0.4-2.2 g / cm 3 , fluidity is 30-50s / 50g.

6. The composite coating according to any one of claims 1 to 5, characterized in that: The material of the bonding layer is metal alloy powder, selected from one or more of NiCrAlYSi, NiCrAlY, NiCrCoAlY, nickel-chromium alloy, and cobalt-chromium alloy, with a thickness of 0.1-0.2 mm; And / or, the bonding layer is a heat-treated bonding layer.

7. The composite coating according to any one of claims 1 to 5, characterized in that: The material of the protective layer is a heat-resistant resin selected from one or more of modified polysilazane resin, modified polysiloxane, modified siloxane, and modified silicone resin, and has a thickness of 0.03-0.05 mm.

8. The composite coating according to any one of claims 1 to 5, characterized in that: The surface layer is made of a wave-transmitting, high-temperature resistant material selected from high-entropy rare earth double silicate (La 1 / 6 Hf 1 / 6 Ta 1 / 6 Yb 1 / 6 Er 1 / 6 G 1 / 6 )2Si2O7, mullite, BSAS (BaO-SrO-Al2O3-SiO2), alumina, YSZ, with a thickness of 0.05-0.1mm.

9. A method for preparing a composite coating according to any one of claims 1 to 5, characterized in that: The method comprises: (1) Spraying bonding layer; (2) Spraying protective layer; (3) spraying a functional layer, wherein the material of the functional layer comprises a thermally sprayed composite ceramic material, wherein the composite ceramic material comprises a matrix material and a plurality of electromagnetic functional materials dispersed in the matrix material; (4) Spraying surface layer.

10. The method according to claim 9, characterized in that: Step (1) also includes heat treating the sprayed bonding layer.

Citation Information

Patent Citations

  • Heat insulation / radar wave absorption integrated composite coating, titanium alloy material with surface coated with composite coating, and preparation method of titanium alloy material

    CN111304578A

  • Caron nanotube / mullite ceramic base multiple phase material and preparation method thereof

    CN1669982A

Cited By

  • Vacuum deposition method for gradient composite coating of contact terminal

    CN121250356A

  • A shunt with electromagnetic interference absorption noise electromagnetic wave function and a manufacturing method thereof

    CN122525191A